De-intensification of postoperative radiotherapy in head and neck cancer irrespective of human papillomavirus status—results of a prospective multicenter phase II trial (DIREKHT Trial) - Haderlein, Marlen; von der Grün, Jens; Balermpas, Panagiotis; Rödel, Claus; Hautmann, Matthias G.; Steger, Felix; Bohr, Christopher; Hehr, Thomas; Stromberger, Carmen; Budach, Volker; Schymalla, Markus; Engenhart-Cabillic, Rita; et al. (Frontiers in Oncology, 2024)
Background Current standard treatment concepts in head and neck squamous cell carcinoma (HNSCC) are based on former studies using 2D and 3D treatment plans. However, modern radiation techniques allow for a more precise and individual dose application. Therefore, in a clearly defined patient population de-intensified risk-adapted radiation is investigated. Methods Patients with newly diagnosed HNSCC after surgery(with resection margins≥1mm and cM0) with the following tumor stages (TNM 7thEdition) were eligible for the study: Oral cavity, oropharynx or larynx: pT1-3, pN0-pN2b, hypopharynx: pT1-2; pN1. The patients should either have a low risk of local recurrence(≤pT2, resection margin ≥5mm, no peritumoral lymphangiosis(L0) and no perineural invasion) or contralateral lymph node metastasis (≤ 3 ipsilateral lymph node metastases, in case of well-lateralized oropharyngeal or oral cavity cancer contralateral cN0, otherwise pN0). Patients were assigned to 3 different treatment regimes with reduction of the treated volume, radiation dose or both, according to tumor stage and results of surgery performed(see Fig1). Primary objective was to show LRR of <10% after 2years. Findings: 150 patients were enrolled. Tumor localisations were: n=53(35·3%) oral cavity, n=94(62·7%) oropharynx (82% HPV-positive), n=2(1·3%) Hypopharynx, n=1(0·7%) Larynx. 61 patients(41·0%) were stage IVA, 81(54·0%) stage III and 8(5·3%) stage II. Median follow up was 36 months. Cumulative incidence of 2y-LRR was 5·6%(95% CI: 1·7%-9·2%) in the whole study population and 14.1%(95%CI: 3.8%-23.2%) in patients with oral cavity cancer. Cumulative incidence of 2y-LRR in non-irradiated or dose-reduced regions was 3·5 %(95% CI: 0·4%-6·5%) After 2 years disease-free survival was 92%(95% CI: 87%-96%), overall survival was 94%(95% CI: 90%-98%) for the complete study cohort. Acute III° toxicity was as follows: dysphagia: 30%, xerostomia: 7%, mucositis 19%, dermatitis: 4%.Dysphagia and xerostomia decreases over time. After 27 months late dysphagia III° and xerostomia II° was 1% and 9%. Interpretation: The study met its primary objective. De-intensification of postoperative radiotherapy irrespective to HPV status in a pre-defined patient population is associated with a favorable toxicity profile without compromising LRR. In an unplanned subgroup analysis, a significantly increased risk of LRR was observed in patients with oral cavity cancer. In these patients, deintensified radiotherapy should be applied with caution.